PENGGUNAAN MODEL COOPERATIVE LEARNING DALAM MENINGKATAN PEMAHAMAN PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA NEGERI 2 KALIPARE KABUPATEN MALANG - Oktavia, Santi (PRODI PAI FIK UNIRA MALANG, 2022)
This study aims to determine how the cooperative learning model in PAI subjects at SMPN 2 Kalipare. To achieve the goal, the researcher used qualitative methods. The data collection methods are observation, interviews, and documentation. Technical analysis of the data using data collection, data reduction, data display and data inference. The results showed that the use of the cooperative learning model at the State Junior High School 2 Kalipare was able to understand students well in Islamic religious education subjects. Students' understanding increases well, it can be seen in terms of the results of students' scores getting better as well as from daily behavior both in the school environment by increasing students' politeness towards teachers and students' activeness in religious activities but still need to improve when at home. Keywords: Cooperative learning, Understanding, Islamic Religious Education